Shark immune system: A review about their immunoglobulin repertoire - C. Gargano; M. Mauro; C. Martino; V. Queiroz; A. Vizzini; C. Luparello; R. Badalamenti; F. Bellistrì; A. Cuttitta; H. Kondo; F. Longo; V. Arizza; et al. (Fish & Shellfish Immunology, 2025)

Exploring priming strategies to improve stress resilience of Posidonia oceanica seedlings - I. Provera; M. Martinez; A. Zenone; V.M. Giacalone; G. D'Anna; F. Badalamenti; L. Marín-Guirao; G. Procaccini (Marine Pollution Bulletin, 2024)

Size-dependent predation of the mesopredator Marthasterias glacialis (L.) (Asteroidea) - P. Gianguzza; F. Di Trapani; C. Bonaviri; D. Agnetta; S. Vizzini; F. Badalamenti (Marine Biology, 2016)

A Mediterranean record of Eulalia ornata (Annelida: Phyllodocidae) corroborating its fidelity link with the Sabellaria alveolata-reef habitat - E. SCHIMMENTI; L. MUSCO; S. LO BRUTTO; B. MIKAC; A. NYGREN; F. BADALAMENTI (Mediterranean Marine Science, 2015)
Among marine habitats Sabellaria alveolata-reefs deserve protection since they provide important ecosystem services and positive effects on biodiversity. Several marine species are listed among the S. alveolata-reef associated fauna, but characteristic species were seldom reported. Eulalia ornata (Annelida, Phyllodocidae) might represent an exception, since it appears common/abundant in S. alveolata-reefs of the Eastern Atlantic. The most evident geographical mismatch in the distributions of E. ornata and these biogenic reefs occurs in the Mediterranean Sea, where S. alveolata-reefs are commonly found, but E. ornata was never recorded, whilst E. viridis, a non-Mediterranean species, was previously listed among the dominant reef-associated taxa. The faunal characterization of the sabellarid reefs along the Sicily Channel revealed an Eulalia species as the dominant taxon associated with that habitat in the area. A taxonomic approach integrated with DNA barcoding, and comparisons with closely related species, allow us to report E. ornata as a new record for the Mediterranean Sea. We describe patterns of abundance and distribution and corroborate its status as a preferential species in the S. alveolata-reef habitat. Focusing on the biology and ecology of E. ornata could help us to better understand the dynamics and functioning of this valuable European shallow marine habitat.

Concern about the spread of the invader seaweed Caulerpa taxifolia var. distichophylla (Chlorophyta: Caulerpales) towards the West Mediterranean - L. MUSCO; F. ANDALORO; B. MIKAC; S. MIRTO; T. VEGA FERNADEZ; F. BADALAMENTI (Mediterranean Marine Science, 2014)
The new Australian alien seaweed Caulerpa taxifolia var. distichophylla, after being established along the Turkish Mediterranean coast in 2006, was recorded in Southern Sicily in 2007. Since then local fishermen claimed support to counteract the effects of entanglement of large amounts of the alien strain wrack in their trammel nets, causing the gear to become ineffective. The further northward and westward spread of the new alien strain is supposed to be limited by winter temperature. We present novel data confirming that the new alien strain is fully naturalized in Central Mediterranean and is expanding its range beyond such limit (i.e. the 15°C February isotherm), thus becoming potentially able to colonize the western basin. By means of a preliminary estimation of effects on native polychaete assemblages, and considering some peculiarities of Sicily (mostly linked to its geographical position in the Mediterranean Sea), the risk linked to the increasing range of distribution of the invasive algae is highlighted.

Size influences the spatial distribution and fish‐aggregating device use of five Mediterranean fish species - M. SINOPOLI; F. BADALAMENTI; G. D’ANNA; M. GRISTINA; F. ANDALORO (Fisheries Management and Ecology, 2011)
Fish‐aggregating devices are floating objects used worldwide to improve pelagic fishery yield. Fish‐aggregating devices use the natural attraction exerted by floating objects on juveniles and adults of both pelagic and demersal fish. In this study, it was hypothesised that fish change their degree and type of interaction with moored floating objects depending on size. This is because fishes in early life stage remain close to floating objects, using them as a shelter, but as they grow they move further away from floating objects spending their time swimming to seek food. To test this hypothesis, the spatial distribution and habitat use of five Mediterranean fish species were quantified. The results enabled the hypothesis to be accepted for all species, except Balistes carolinensis Gmelin. For this species, a shelter from predator model was applicable, but for the other species, the generalised meeting point model was more adaptable.

Leading role of the sea urchin Arbacia lixula in maintaining the barren state in southwestern Mediterranean - C. Bonaviri; T. Vega Fernández; G. Fanelli; F. Badalamenti; P. Gianguzza (Marine Biology, 2011)

Shelter selection of the spiny lobster Palinurus elephas under different levels of Octopus vulgaris predation threat - M. Gristina; M. Sinopoli; F. Fiorentino; G. Garofalo; F. Badalamenti (Marine Biology, 2011)

Shelter preference in captive juveniles of European spiny lobster Palinurus elephas (Fabricius, 1787) - Michele Gristina; F. Fiorentino; G. Garofalo; F. Badalamenti (Marine Biology, 2009)

Limited trophodynamics effects of trawling on three Mediterranean fishes - F. Badalamenti; C. J. Sweeting; N. V. C. Polunin; J. Pinnegar; G. D’Anna; C. Pipitone (Marine Biology, 2008)

FADs influence on settlement and dispersal of the young-of-the-year greater amberjack (Seriola dumerili) - M. Sinopoli; G. D’Anna; F. Badalamenti; F. Andaloro (Marine Biology, 2007)

Relationship between egg features and maternal body size in the simultaneous hermaphrodite Oxynoe olivacea (Mollusca, Opisthobranchia, Sacoglossa) - P. Gianguzza; K. R. Jensen; F. Badalamenti; S. Riggio (Marine Biology, 2005)

Colonisation process of vegetative fragments of Posidonia oceanica (L.) Delile on rubble mounds - G. Di Carlo; F. Badalamenti; A. C. Jensen; E. W. Koch; S. Riggio (Marine Biology, 2005)

Effects of fish feeding by snorkellers on the density and size distribution of fishes in a Mediterranean marine protected area - M. Milazzo; F. Badalamenti; T. Vega Fernndez; R. Chemello (Marine Biology, 2005)

Size-related trophodynamic changes in three target fish species recovering from intensive trawling - Badalamenti F.; D'Anna G.; Pinnegar J.; Polunin N. (Marine Biology, 2002)